1997
DOI: 10.1002/anie.199701561
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Coordination Chemistry of Fluorine‐Containing Cages

Abstract: COMMUNICATIONS tion, one of the methoxy resonances was shifted upfield to b = 3.28 as a result of shielding of the methoxy group by the neighboring phenyl ring.r1b1 This group occupies a nearly orthogonal position, which would also explain the absence of dilactone formation after closure of the first lactone ring.In the final synthetic step a n intramolecular Pd-catalyzed Heck reaction was applied for the formation of the isoquinoline ring. This reaction afforded lamellarin G trimethyl ether (8) in 74 YO yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Candidate data sets include a diverse array of Lewis acidic sites, including multiple group 1 and 2 elements (lithium, ,, sodium, ,, potassium, , rubidium, cesium, , and calcium), as well as several transition elements (zirconium, , hafnium, and palladium). The aggregate data qualitatively agree with the statement that stronger C–F···LA interactions lead to lower 1 J C,F values: a simple plot of observed 1 J C,F versus coordinated C–F bond length shows a downward trend which, when fit to an empirical linear model ( R 2 = 0.64), suggests that 1 J C,F values decrease at a rate of about 6 Hz per 0.01 Å elongation (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate data sets include a diverse array of Lewis acidic sites, including multiple group 1 and 2 elements (lithium, ,, sodium, ,, potassium, , rubidium, cesium, , and calcium), as well as several transition elements (zirconium, , hafnium, and palladium). The aggregate data qualitatively agree with the statement that stronger C–F···LA interactions lead to lower 1 J C,F values: a simple plot of observed 1 J C,F versus coordinated C–F bond length shows a downward trend which, when fit to an empirical linear model ( R 2 = 0.64), suggests that 1 J C,F values decrease at a rate of about 6 Hz per 0.01 Å elongation (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Candidate data sets include a diverse array of Lewis acidic sites, including multiple group 1 and 2 elements (lithium, 13,28,29 sodium, 13,30,31 potassium, 13,32 rubidium, 33 cesium, 16,34 and calcium 35 ), as well as several transition elements (zirconium, 29,36 hafnium, 29 and palladium 37 ).…”
Section: The General Relation Between δ 1 Jcf and C−f Bond Activationmentioning
confidence: 99%
“…In our hands, mono-O-benzylation of 2,2,3,3-tetrafluorobutane-1,4-diol (1) afforded 2 in 58% isolated yield. Subsequent base promoted reaction of 2 (2 equivalents) with 3,5-bis(2'-tosyloxyethyl)-4-oxahexacyclo[5.4.1.0 2,6 .0 3,10 .0 5,9 .0 8,11 ]-dodecane (3) 13 produced 4 (62% yield).…”
Section: Synthesis Of Fluorinated Podands and Crown Ethersmentioning
confidence: 99%
“…6 The high electronegativity and hardness of fluorine 7 render covalently bonded fluorine (C-F) suitable as an electron-pair donor for complexation with hard acceptors, e.g., alkali metal (Group I) and alkaline earth (Group II) metal cations, respectively. 8 Hitherto, we have demonstrated that cage-annulated crown ethers, 9 cryptands,clefts, 11 and molecular boxes, 12 constitute a new class of host systems for the study of host-guest interactions (i.e., molecular recognition and inclusion phenomena). Recently, we have undertaken the synthesis of some fluorine-containing analogs of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 Additionally, organofluoro ligands can be more powerful than oxygen ligands in coordinating metals. 8 Whereas enantiocontrolled syntheses of monofluoroorganic compounds are well established, synthesis of an enantiopure vicinal difluoro compound, especially of C 2 symmetry, has not to the best of our knowledge been reported prior to this communication. 9,10 Generally, molecular fluorine adds to alkenes with syn-stereoselection, thereby precluding the formation of C 2 symmetric difluorides; 11 where trans-addition is observed yields are usually low.…”
mentioning
confidence: 97%